Habitat Use and Movements of a Blanding's Turtle Population in Central Wisconsin - Ross, David A. (University of Wisconsin-Stevens Point, College of Natural Resources, 1985)
Eight radio-tagged Blanding's turtles, monitored from June 1983 to January 1984 showed high use of a cattail marsh (101 turtle-days) and a sparsely vegetated pond (88 turtle-days). Most inhabited wetlands were less than 60 cm deep and had summer water temperatures below 28.5 degrees C. Five of 8 turtles used different and disjunct habitats between June to September, then moved to 2 adjacent deep ponds for overwintering. Five overwintering sites contained either standing or flowing water, silt bottoms and water depths greater than 0.5 m. Size of activity centers of 2 males (0.57 and 0.94 ha) was not significantly different from that of 6 females (x=0.56 ha). Total range lengths of 2 males (260 m and 635 m) were not significantly different from that of 6 females (489 m). Fourteen of 16 nests (87.4%) nests were in grasslands. Mean nest distance from water and activity centers were 168 m and 620 m, respectively. Striped skunks (Mephitis mephitis) destroyed at least 9 of 16 nests. At least 4 nests were destroyed by predators within 24 hours of completion~ all nests were eventually destroyed by predators.